Towards a Model of Situated Acceptance of Tablets in Teaching Practice in Moroccan Primary Schools - Rahali, El Ayachi; El Khattabi, Khalid; Chikhaoui, Ahmida; Ouzennou, Fatima (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This article aims to contribute to the establishment of a model of tablets’ situated acceptance in teaching practice in Moroccan primary schools. To do this, Davis’ TAM has been adopted in the testing of this technology in its context of use. This research is conducted through a questionnaire administered in six primary schools in the region of Béni Mellal-Khénifra, one of the twelve regions of Morocco. An exploratory factorial analysis and another confirmatory one using structural equation modelling revealed that the appropriation of tablets is positively and directly influenced by the perception of its usefulness in teaching practice; and indirectly by teacher training and conditions that facilitate teachers’ work.